Commercial unit in the border area. An analysis of the impact of Chilean consumption on cash flows in companies from Tacna - Díaz Zelada, Yvan (2020)
The cities of Tacna and Arica make up the geographical border between Peru and Chile. Both cities have developed economic and commercial activities during the year. This border context has made many businesses in the city of Tacna, are favored with a significant increase in their cash flows as a result of consumption by the Chilean citizen. For many entrepreneurs, this constant income of money has become the main economic flow for their businesses and the main source of income for their families.